Implementation of Student Course Evaluation: Pandemic Impact on the Non-Constraint Engagement (NCE) Model - Faridah Maarof; Said El-Emam; Raudah Mohd Yunus (International Journal of Management and Data Analytics)
Traditionally, students’ feedback in the form of Student Course Evaluation (SCE) has been paper-based and made mandatory on students. Even when SCE is made online and voluntary, one major obstacle is low response rate. The Non-Constraint Engagement (NCE) Model is a newly introduced method in enhancing SCE in our institution, that attempts to overcome the common limitations of SCE. This study aims to examine the stability and sustainability of the NCE model implementation before, during and after the peak of the first wave of the COVID-19 pandemic in the Canadian University Dubai (CUD). The NCE Model was initially piloted between 2014 and 2015 and was found to be effective. To test its feasibility and sustainability over a longer period of time, an SCE exercise was implemented among undergraduate students across four faculties. For analysis, we used SCE data from 2015 to 2021. Evaluations were performed via Moodle in the online Learning Management System (LMS) before mid-term of each semester. There were two domains of SCE: course rating and instructor rating. Results showed acceptable and stable response rates, despite SCE being voluntary. The COVID-19 pandemic did not cause a fall in student participation. Instead, following the outbreak arrival, there was a sharp increase in SCE response rates. Similarly, students’ rating on their courses and instructors remains high despite the massive, sudden change from physical to online instruction. This study introduces a new approach, the NCE model, which can be tested in other educational settings to enhance SCE.